(untitled) (Research, Society and Development, 2021)
Babassu mesocarp starch (Attalea speciosa Mart. Ex Spreng) and Aloe vera (Aloe vera (L.) Burm. f.) Are natural materials with wide application in the health fields. In this research work, casting films composed of babassu mesocarp starch supplemented with Aloe vera in the proportions of 0%, 5%, 8% and 10% were prepared and characterized, observing physical characteristics of thickness, humidity, water solubilities, vapor permeability of water and mechanical properties. In addition, the cytotoxicity of the filmogenic solution was evaluated in murine macrophages of the RAW 264.7 strain and human red blood cells. The results show that the developed films have a smooth surface, good malleability and are self-supporting. The moisture content, solubility and water vapor permeability increased according to the increase in the concentration of Aloe vera, for the mechanical properties there was no significant difference (p> 0.05) between the formulations tested. The filmogenic solution showed a cytotoxic effect considered safe for human macrophages and red blood cells. These characteristics demonstrate a good potential for wound coverage and tissue repair.